(untitled) (Journal of Engineering, 2018)
The research focuses on how to reach a mechanism that assists experts, engineers, and others in the architectural & engineering project to verify the co-existence of values and sustainability constituents in it. Research problem shows a clear lack, locally, in the interest to establish a value system and a list that cares about comprehending building components whether considering sustainable building criteria. Hypothesis shows that in order to head towards the applicable sustainable approach of buildings, then a local assessment system should be established to evaluate buildings during its life cycle, and from which buildings would be categorized as sustainable or not. Research aims at establishing main and general concepts that form the basis for more accurate assessment elements and details that have weights and credits to reach assessment scores that enables recognizing if the building or the project considers environmental sustainability requirements, in addition to submitting special recommendations that provide the capability of establishing an integrated usable assessment system used by experts and others. The research adopts the following methodology in order to obtain and reaches this list: a comprehensive and thorough study for the main international assessment systems; a study for certain research and papers involved in the assessment topic; inspecting practices of sustainability-related consultancy professional work. All this to determine the constituents of rating and evaluation of the engineering project items and components. Moreover, research adopts a methodology that considers local recognition in terms of social and climatic environment and geographical factors. Research reaches the formation of a general framework that is compromised from general and secondary indicators for the local assessment system, and these indicators could be expanded to include the building entire life cycle.